A study on the evolution of sexual receptivity and plasma estradiol-17beta levels throughout the lactation period, in rabbits - Ubilla E.; Rebollar P.G. (Rabbit production in hot climates, 1994)
This study was designed to determine the evolution of plasma estradiol 17-beta (E2) levels and sexual receptivity (S.R.), from days 1 to 30 of the lactation period in rabbits. E2 and S.R. were measured daily in 12 lactating doe rabbits of the California x New Zealand breed with 7-10 pups/litter. E2 levels were determined by immunoassay (ELISA), and S.R. by means of turgidity and color of the vulva. High means of plasma E2 concentrations were found on days 1, 5 to 7 and 23 to 30 of the post-partum period (P.P.),(p less than 0.001), and low E2 levels on days 13 to 23 of the P.P. (p less than 0.05), when comparing to the general mean E2 level (11.7 + or - 0.3 pg/ml). 75 per cent of the does showed high S.R. on day 1 after parturition (p less than 0.001). High and medium S.R. were observed in most of the females (80 per cent) on days 2, and 25 to 30 of the P.P. (p less than 0.05). Mean plasma E2 levels differed in does with high S.R. compared to animals with medium or low S.R. (15.2 + or - 0.13 pg/ml vs. 11.4 + or - 0.10 pg/ml and 11.5 + or - 0.12 pg/ml, respectively; (p less tha 0.05). Correlation of plasma E2 concentrations with S.R. was not significant. The results suggest the presence of at least three high plama E2 concentration intervals and two periods of increased S.R. in lactating non-pregnant rabbits throughout the postpartum days. Mean plasma E2 levels differed in does with high S.R. compared to animals with medium and low S.R. Sexual behaviour appeared to be influenced by the lactation period, probably via prolactin levels.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)